Templating effect of trans-2, 5-dimethylpiperazine (TDMP) on the structural dimensionality of hybrid metal halides. Issue 28 (25th May 2022) - Gautier, Romain; Paris, Michael; Massuyeau, Florian
Abstract : The templating effect of trans -2, 5-dimethylpiperazine on the structures of 13 metal halide compounds has been investigated. The oxidation state and coordination sphere of the metal ions are the two key parameters related to the dimensionality of the inorganic network. Abstract : Templating effects are commonly investigated by comparing different organic structure-directing agents in a specific inorganic system. Herein, a specific secondary diamine, the trans -2, 5-dimethylpiperazine, has been selected for different metal halide anions with the aim to analyze its influence on different inorganic networks. Thus, five new trans -2, 5-dimethylpiperazine-1, 4-diium based compounds with [CuBr4 ] 2−, [CdBr4 ] 2−, [CuBr2 ] −, [AgCl2 ] −, and [AgBr2 ] − have been synthesized, structurally characterized and compared to eight previously reported compounds containing [ZnCl4 ] 2−, [ZnBr4 ] 2−, [CoCl4 ] 2−, [PbCl4 ] 2−, [PbBr4 ] 2−, [SnBr4 ] 2−, [CuCl4 ] 2−, and [CdCl4 ] 2− . Despite the different crystal structures (space-groups, inorganic frameworks, etc .), the dimensionalities (from 0D to 2D) of the inorganic networks of these 13 hybrid materials could be rationalized according to only two parameters: the oxidation state (+1 or +2) and the coordination sphere (tetrahedron or octahedron) of the metal ions. The luminescence properties of the new hybrid silver bromide have been analyzed and discussed by comparing the luminescence mechanisms of the other previously reported trans -2, 5-dimethylpiperazine-1, 4-diium metal halides.